PATIENT SAFETY CULTURE IN CLINICAL CARE SETTING: A LITERATURE REVIEW - Suciati Suciati; Nurfika Asmaningrum; Suhari Suhari (UPT Penerbitan Universitas Jember, 2023)
Background: Patient safety is currently the most important global issue where many patient claims are reported for medical errors that occur in patients. Steps to overcome this with a culture of safety in health care. Methods: This research is a literature review. This study complies with PRISMA standards. Data sources for the identification of Science Direct, Pubmed, Scopus, and Google Scholar from 2013 to 2023. The keywords used include